Differential regulation of Type 1 and Type 2 mouse eosinophil activation by apoptotic cells - Dolitzky, Avishay; Hazut, Inbal; Avlas, Shmulik; Grisaru-Tal, Sharon; Itan, Michal; Zaffran, Ilan; Levi-Schaffer, Francesca; Gerlic, Motti; Munitz, Ariel (Frontiers in Immunology, 2022)
Eosinophils are multifunctional, evolutionary conserved leukocytes that are involved in a plethora of responses ranging from regulation of tissue homeostasis, host defense and cancer. Although eosinophils have been studied mostly in the context of Type 2 inflammatory responses, it is now evident that they participate in Type 1 inflammatory responses and can respond to Type 1 cytokines such as IFN-gamma. Notably, both Type 1- and Type 2 inflammatory environments are characterized by tissue damage and cell death. Collectively, this raises the possibility that eosinophils can interact with apoptotic cells, which can alter eosinophil activation in the inflammatory milieu. Herein, we demonstrate that eosinophils can bind and engulf apoptotic cells. We further show that exposure of eosinophils to apoptotic cells induces marked transcriptional changes in eosinophils, which polarize eosinophils towards an anti-inflammatory phenotype that is associated with wound healing and cell migration. Using an unbiased RNA sequencing approach, we demonstrate that apoptotic cells suppress the inflammatory responses of eosinophils that were activated with IFN-gamma + E. coli (e.g., Type 1 eosinophils) and augment IL-4-induced eosinophil activation (e.g., Type 2 eosinophils). These data contribute to the growing understanding regarding the heterogeneity of eosinophil activation patterns and highlight apoptotic cells as potential regulators of eosinophil polarization.